Pengembangan Aplikasi Pengelolaan Pusat Layanan Pada Palang Merah Indonesia (PMI) Wilayah Jakarta Timur - Parulian, Dudi Parulian; Mohammad Fazrie (Elkom: Jurnal Elektronika dan Komputer, 2024)
The management of service centers at the Indonesian Rede Cross (PMI) in East Jakarta is still conducted manually, which slows down service processes and increases the likelihood of data processing erorrs. This research aims to design a Java-based application to automate patient registration, admission, handling, emergency services, available ambulance data, and the preparation of reports as quickly as possible. The application was developed using the Java programming language with a prototype model approach in software development. Testing results indicate that this application successfully enhances the efficiency and accuracy of PMI East Jakarta’s operations, particularly in managing data related to patients, actions, personnel, and ambulance availability. It is hoped that this application can be integrated with other PMI regions to establish a more structured and connected service management system.